Pengaruh Penggunaan Media Sosial Tiktok terhadap Peningkatan Prestasi Akademik Mata Pelajaran Aqidah Akhlak Siswa MI Al Hijrah Bontang Tahun Pelajaran 2024/2025 - Syafitri, Inindah; Minarsih, Minarsih (Sekolah Tinggi Ilmu Tarbiyah Syamsul Ma'arif Bontang, 2025)
The development of information technology and social media, particularly TikTok, has become an inseparable part of students' daily lives, including in the context of education. Social media has a dual influence on students, both in terms of enhancing academic achievement and shaping moral character. TikTok can be utilized as a creative and engaging learning medium, especially in the subject of Aqidah Akhlak. This study aims to examine the influence of TikTok social media usage on improving academic performance in the Aqidah Akhlak subject among students in grades I–VI at MI Al Hijrah Bontang for the 2024/2025 academic year. This research employs a quantitative approach with a total of 63 student respondents. Data collection techniques include interviews, questionnaires, observations, and documentation. The data were analyzed using validity and reliability tests, correlation coefficients, coefficient of determination, and hypothesis testing. The results show a very strong relationship between TikTok usage and students’ academic achievement in Aqidah Akhlak, with a correlation coefficient (r) of 0.845. The determination test indicates that the influence of variable X on variable Y is 71%, while the remaining 29% is influenced by other factors. Hypothesis testing shows that the calculated t-value (12.36) is greater than the critical t-value (1.99962), thus H₀ is rejected and Hₐ is accepted. Therefore, it can be concluded that the use of TikTok social media has a significant influence on improving academic performance in the Aqidah Akhlak subject for students at MI Al Hijrah Bontang in the 2024/2025 academic year.